Carbon-cobalt nanostructures as an efficient adsorbent of malachite green - Hammud, Hassan H.; El Hamaoui, Bassem; Noubani, Nada H.; Feng, Xingliang; Wu, Zhong Shuai; Müllen, Klaus; Ayub, Khurshid (Nanoscience and Nanotechnology - Asia, 2018)
Carbon-cobalt nanostructures 1 and 2 were prepared by pyrolysis of the cis-dichlorobis(1,10-phenanthroline-N,N')-cobalt(II) complex 3 in the absence or presence of anthracene respectively. DFT calculation was used to estimate ligand dissociation energy of cobalt complex, the energy cost for the formation of cobalt particles which catalyze the formation of carbon nanostructures. FE-SEM analysis indicates that 1 and 2 contain 3D nanostructure hierarchical porous graphitic carbons HPCGs wrapping cobalt particles in spheres and rods, with mesopores and macropores ranging from 10-100 nm. TEM analysis indicated that nanostructures 1 and 2 consist of graphite layers as well as single wall and bamboo multiple wall carbon nanotubes. Crystalline cobalt catalyst nanoparticles were found wrapped in ordered graphene layers and also at the tips of the bamboo-shaped disordered multiwall carbon nanotubes. TEM also showed porous surfaces. Both nanostructures 1 and 2 were used as adsorbents to uptake malachite green dye (MG) from aqueous solution. Adsorption isotherms of MG by adsorbents 1 and 2 were fitted in terms of Langmuir, Freundlich, Temkin, and D-R models. The adsorption capacity of 2 (492 mg/g) was higher than that of 1 (200 mg/g). Thermodynamic adsorption studies indicated that the sorption process was spontaneous and exothermic. A pseudo-first order model has been adopted to describe the kinetics of the adsorption process as well as the activated thermodynamic parameters. Column kinetic adsorption of MG by 2 was best fitted by the Thomas model. The column capacity was found to be 64 mg. The adsorbent can be regenerated and proved efficient for three consecutive cycles.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Adsorption isotherm; Carbon nanostructure; Cobalt complex; Column; Complexation energy; Kinetic; Malachite green; Thermodynamics